A rare mutation on alpha-1 antitrypsin deficit and lung fibrosis: case report - Afonso, Miguel; Silva, Clara; Pinho, Inês; Vale, Artur; Fernandes, Ana (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Alpha1-antitrypsin deficiency (AATD) is an autosomal codominant disease, and different genetic variants are known, some of which very rare. Usual pulmonary manifestations are emphysema, bronchiectasis and asthma. Pulmonary fibrosis is uncommon. We describe a case of a 64 year old man with an inaugural diagnosis of cirrhosis and lung fibrosis, without emphysema or bronchiectasis, associated with AATD. Further investigation identified a rare mutation in heterozigosity (MMPalermo), usually associated with liver disease. Concomitantly, he had a secondary iron overload, and in the course of the investigation, a type 2 diabetes mellitus installed.The association between AATD and pulmonary fibrosis is rare, however it has been identified in a few studies and case reports, questioning the role of AAT in pulmonary fibrosis.